THU0561 CANAKINUMAB FOR THE TREATMENT OF ADULT ONSET STILL'S DISEASE TO ACHIEVE REDUCTION OF ARTHRITIC MANIFESTATION AT WEEK 12: AN INVESTIGATOR-INITIATED MULTI-CENTRE, PLACEBO-CONTROLLED STUDY (CONSIDER). (June 2019) - Kedor, Claudia; Listing, Joachim; Zernicke, Jan; Weiß, Anja; Behrens, Frank; Blank, Norbert; Henes, Jörg; Kekow, Jörn; Rubbert-Roth, Andrea; Schulze-Koops, Hendrik; Seipelt, Eva; Specker, Christof; et al.
Abstract : Background: Inhibition of interleukin-1 (IL-1) represents a promising treatment option in adult-onset Still's disease (AOSD). Canakinumab (CAN) is approved for treatment of systemic juvenile idiopathic arthritis (sJIA) since 2013 and recently for AOSD in Europe. In sJIA, CAN has a proven marked impact on systemic and articular disease activity, but for AOSD RCT data is limited. Objectives: Investigation of efficacy and safety of CAN in AOSD patients with joint involvement by means of a multi-centre, double-blinded, randomized, placebo controlled trial. Methods: AOSD patients with joint involvement (tender and swollen joint count ≥4 each) were stratified by pre-treatment status with biologics and randomized in a ratio of 1:1 to CAN (4 mg/kg up to a maximum of 300 mg) or placebo (PBO) s.c. every 4wks. The primary endpoint was defined as the proportion of patients with a clinical-relevant reduction (≥1.2) in disease activity as measured by change in disease activity score (DAS28) at week 12. There were two major protocol violations: two PBO patients received blinded CAN at week 4. Therefore, a per-protocol (PP) analysis, which excluded data of these two patients, was performed. Results: The study was prematurely stopped with 35 out of 68 planned patients enrolled due to approval of CAN for AOSD by EMA. At enrollment, mean DAS28 represented high disease activity for both: 5.4 in CAN (n=18) and 5.3 in PBO (n=17). In the intention-to-treat analysis, 12 (67%) CAN and 7 (41%) PBO patients met the primary endpoint. The 25.5% [95%CI: -10.3%; 55.9%] difference in the response rate did not achieve statistical significance (p=0.18). Using the PP analysis, the treatment difference for primary endpoint was 33.4% [95%CI: -10.3%; 55.9%, p=0.08]. We observed higher ACR50 (50% CAN vs. 6.7% PBO, p= 0.009), ACR70 (28% CAN vs. 0% PBO, p=0.049) response rates, (PP analysis). Higher mean improvements in the CAN vs PBO group for DAS28(ESR and CRP), ESR, CRP, 66 swollen and 68 tender joint counts at week 12 were observed (PP analysis). There were 47 and 21 non-serious adverse events (AE) reported in CAN and PBO groups, respectively. Two CAN patients experienced an SAE (hepatotoxicity and patellofemoral pain syndrome). Conclusion: Although the study was terminated prematurely and the primary endpoint did not achieve statistical significance, treatment of patients with active AOSD with CAN led to improvement of several outcome measures. In addition, safety profile was similar to that reported in sJIA and no unexpected safety issues were observed. This data support the treatment of AOSD patients with CAN. References: [1] Ruperto. NEJM (2012): 2396-2406 Disclosure of Interests: Claudia Kedor Grant/research support from: Sobi, Consultant for: Novartis, Speakers bureau: Novartis, Roche, Joachim Listing: None declared, Jan Zernicke: None declared, Anja Weiß: None declared, Frank Behrens Grant/research support from: AbbVie, Pfizer, Roche, Chugai, Prophylix, Bioline, Novartis, Consultant for: AbbVie, Pfizer, Roche, Chugai, UCB, Bristol-Myers Squibb, Celgene, MSD, Novartis, Biotest, Janssen, Genzyme, Eli Lilly, Speakers bureau: Ad board: AbbVie, Pfizer, Roche, Chugai, UCB, Bristol-Myers Squibb, Celgene, Novartis, Biotest, Janssen, Genzyme, Eli Lilly, Norbert Blank Grant/research support from: SOBI and Novartis, Speakers bureau: Novartis and SOBI, Jörg Henes: None declared, Jörn Kekow: None declared, Andrea Rubbert-Roth Consultant for: Chugai, Eli Lilly, Roche, and Sanofi, Speakers bureau: AbbVie, Bristol-Myers Squibb, Chugai, Hexal/Novartis, Janssen, Eli Lilly, Merck Sharp & Dohme, Pfizer, Roche, and Sanofi, Hendrik Schulze-Koops Grant/research support from: Novartis, Pfizer, Roche, Consultant for: Abbvie, Actelion, Amgen, AstraZeneca, Biogen International, BMS, Celgene, Chugai, GSK, Hospira, Janssen-Cilag, Leo Pharmaceuticals, Lilly, MSD, Medac, Merck, Novartis, Pfizer, Hexal Sandoz, Sanofi, Roche, UCB, Paid instructor for: Abbvie, Actelion, Amgen, AstraZeneca, Biogen International, BMS, Celgene, Chugai, GSK, Hospira, Janssen-Cilag, Leo Pharmaceuticals, Lilly, MSD, Medac, Merck, Novartis, Pfizer, Hexal Sandoz, Sanofi, Roche, UCB, Speakers bureau: Abbvie, Actelion, Amgen, AstraZeneca, Biogen International, BMS, Celgene, Chugai, GSK, Hospira, Janssen-Cilag, Leo Pharmaceuticals, Lilly, MSD, Medac, Merck, Novartis, Pfizer, Hexal Sandoz, Sanofi, Roche, UCB, Eva Seipelt: None declared, Christof Specker: None declared, Eugen Feist Grant/research support from: Pfizer, Roche, Novartis, BMS, Sanofi, Lilly, Consultant for: Pfizer, Roche, Novartis, BMS, Abbvie, Celgene, Sanofi, MSD, Lilly, Speakers bureau: Pfizer, Roche, Novartis, BMS, Abbvie, Celgene, Sanofi, Lilly